Design of a wideband filtering power divider with good in‐band and out‐of‐band isolations. Issue 7 (23rd March 2019) - Liu, Yun; Sun, Sheng; Yu, Xi; Wu, Yongle; Liu, Yuanan
ABSTRACT: In this article, a wideband filtering power divider with good in‐band and out‐of‐band isolations is designed based on a hybrid Wilkinson and Gysel structure. To achieve a good in‐band response, two additional in‐band transmission poles can be introduced by installing the coupled‐line structures at each port. By mounting a stepped impedance open stub at the input port, two transmission zeros are generated near the passband to improve the passband skirt. Furthermore, the out‐of‐band rejection and isolation are achieved by the other two transmission zeros, which are produced by the open stub and the three coupled‐line sections mentioned above. Additionally, a good in‐band isolation is realized by the isolation resistor between output ports. For the demonstration, a wideband filtering power divider centered at 1.5 GHz with a 56% fractional bandwidth and 20‐dB isolation is designed and fabricated. The simulated and measured results are in good agreement with each other.